The Effects of Rural-Urban Migration on Rural Communities of Southeastern Nigeria. (9th September 2013) - Ajaero, Chukwuedozie K.; Onokala, Patience C.
Abstract : This paper examined the effects of rural-urban migration on the rural communities of Southeastern Nigeria. Data were obtained using mixed methods approach comprising questionnaire surveys and key informant interviews. Six rural local government areas (LGAs) were selected based on population size and spatial equity from two states of Southeastern Nigeria. From each of the rural LGAs, fifty migrant-sending households were sampled for the study. Multiple regression and hierarchical cluster analyses were used to estimate and categorize the effects of rural-urban migration due to remittances and community projects executed by the rural-urban migrants, respectively. In addition, the Chi-square and Kruskal-Wallis tests were utilized in prioritizing areas for development interventions in the rural communities. The regression analysis shows that rural-urban migration contributes significantly towards the development of their rural communities through monetary remittances and the involvement of the rural-urban migrants in community development projects. Based on the findings, recommendations such as initiation of development projects based on the identified needs of each of the rural communities to augment the effects of migration in the study area are made.